Effectiveness of a Malaysian Media Intervention Workshop: Safe Reporting on Suicide - Lim, Jane Tze Yn; Cheng, Qijin; Ng, Yin Ping; Pheh, Kai Shuen; Panirselvam, Ravivarma Rao; Tay, Kok Wai; Lim, Joanne Bee Yin; Chan, Wen Li; Amer Nordin, Amer Siddiq; Zakaria, Hazli; Bartlett, Sara; Skehan, Jaelea; et al. (Frontiers in Psychology, 2021)
Background: Suicide remains an important cause for premature deaths which draws media attention. However unsafe reporting and portrayal of suicides by the media have been associated with increased risk of suicidal behaviour. Current evidence suggests that media capacity-building is potentially suicide preventive. However, there are still knowledge gaps in terms of lack of data on effective strategies to improve the awareness and implementation of safe reporting of suicide-related media content. This study aims to investigate the effectiveness of a workshop conducted for media community on safe reporting of suicide-related content. Methods: An interventional single-arm pre and post pilot study was conducted on a sample of Malaysian media community recruited through purposive and snowball sampling. The media safe reporting workshop was conducted by a suicide prevention expert with media industry background. Thirty participants completed a self-reported evaluation questionnaire on their awareness and knowledge on reporting suicide-related media content; before and after the interventional workshop. Results: There was a significant difference between the total scores before and after intervention, with a large effect size. Post intervention scores were significantly improved in 8 items, namely those related to reporting of (i) contents of any suicide note; (ii) headlines with methods of suicide; (iii) headlines with location of suicide; (iv) cases of suspected suicide despite the unconfirmed cause of death; (v) suicide news to cater to readers’ interests; (vi) cause of suicide; (vii) details of location of suicide and (viii) negative impact to media community when reporting suicide stories. In particular, the improvement on majority of the items were significant for media community with no lived experience of suicidal behaviour. Conclusion: The media safe reporting workshop has potential as an effective intervention for improving the awareness and knowledge measures of safe suicide reporting among the media community, with a more pronounced effect in those without lived experience of suicidal behaviour. Limitations on the sample size, generalisability, short-term evaluation and lack of a control group warrant future larger, longer-term controlled and more representative studies.